1999
DOI: 10.1111/j.1540-8159.1999.tb00408.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Precise Origin of Idiopathic Ventricular Tachycardia from the Right Ventricular Outflow Tract by a 12‐Lead ECG: A Study of Pace Mapping Using a Multielectrode “Basket” Catheter

Abstract: Radiofrequency catheter ablation guided by pace-mapping techniques has proven effective in eliminating idiopathic ventricular tachycardia (VT) originating from the right ventricular outflow tract (RVOT). A method for rapidly identifying the origin of VT from 12-lead electrocardiogram (ECG) findings would be helpful for the catheter ablation procedure. The purpose of this study is to precisely localize the origin of idiopathic VT from the RVOT by a 12-lead ECG from a study of multipoint pace mapping. In one pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 15 publications
0
19
0
1
Order By: Relevance
“…Although several studies have described the ECG characteristics of OT-VT/PVC originating from the free wall of the RVOT, 3,4,14,15 we have not found any that determined the prevalence and ECG characteristics of VT originating from the RVOT free wall in a considerable number of patients.…”
Section: Previous Studiesmentioning
confidence: 74%
See 1 more Smart Citation
“…Although several studies have described the ECG characteristics of OT-VT/PVC originating from the free wall of the RVOT, 3,4,14,15 we have not found any that determined the prevalence and ECG characteristics of VT originating from the RVOT free wall in a considerable number of patients.…”
Section: Previous Studiesmentioning
confidence: 74%
“…Two paced mapping studies found the QRS morphology in lead I to be useful in distinguishing a posterior from anterior origin of OT-VT/PVC, and that an RS or a QS pattern of QRS morphology in lead I indicated the leftward and anterior sites of the RVOT free wall. 14,15 Few studies have considered the relationship between the QRS morphology in lead I and the specific location of a tachycardia focus within the free wall in patients with FW-VT/PVC; 14,15 of them, Dixit et al reported that only 1 of 7 FW-VT/PVC cases showed an origin from the anterior portion of the RVOT free wall. 14 In the present study, however, all FW-VT/PVC showed an RR' pattern in lead I, indicating a likely origin in the posterior portion of the RVOT free wall.…”
Section: Previous Studiesmentioning
confidence: 99%
“…The RVOT-VPCs with a positive QRS wave in lead I usually arise from the posterior attachment side of the septum or free wall. 11 As shown in Figure 4, in 9 of 14 patients, the final successful ablation sites in the present study were also on the posterior attachment of the RVOT.…”
Section: Ecg Characteristics Of the First Vpc Initiating The Pvtmentioning
confidence: 80%
“…70,71 Deeper S waves in aVL than in avR suggest a leftward superior focus, and this ratio decreases with sites located more rightward and inferior in RVOT. 72 Precise localization relies on combined use of pace mapping and activation mapping. In most patients, a site with a pace map QRS that exactly matches that of VT can be identified at or very close to the VT focus, but excellent pace maps may be obtained several millimeters distant from the earliest activation.…”
Section: Rvot Tachycardiamentioning
confidence: 99%